2012
DOI: 10.3390/admsci2010047
|View full text |Cite
|
Sign up to set email alerts
|

Regionalizing Immigration, Health and Inequality: Iraqi Refugees in Australia

Abstract: Humanitarian immigrants and refugees face multiple adjustment tasks and post-settlement support services concentrated in metropolitan areas play an important role. As part of an ongoing commitment, the Australian Government has increasingly supported resettlement in rural and regional areas of the country. Drawing on the experience of Iraqi migrants in Victoria, Australia, we examine some of the conditions that characterize regional resettlement and raise key questions for public health policy. Structural vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Racism impacted on people's lives, particularly those from Africa, undermining a sense of belonging, safety, and in turn effective integration [76,77]. There is a substantial literature highlighting the detrimental impact of racism on health in general [78][79][80][81][82] as well as for refugees specifically [57,[83][84][85][86], including in rural resettlement [41,76,77,87]. Community development initiatives such as community arts projects and anti-racism curriculum in schools are important in these contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Racism impacted on people's lives, particularly those from Africa, undermining a sense of belonging, safety, and in turn effective integration [76,77]. There is a substantial literature highlighting the detrimental impact of racism on health in general [78][79][80][81][82] as well as for refugees specifically [57,[83][84][85][86], including in rural resettlement [41,76,77,87]. Community development initiatives such as community arts projects and anti-racism curriculum in schools are important in these contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Research investigating the broad resettlement experiences for people from refugee backgrounds in high income countries has proliferated in recent years [54], however less research has focused on the experiences of refugees in regional or rural areas, particularly regarding health in those environments [55], and there is very limited research outside Australia on the experiences of refugees in regional or rural areas. The research that has been conducted has indicated that successful settlement is dependent on a number of factors [11,47,56,57] such as attitudes of the host community [41]; rural employment opportunities [58]; and size and connections of the incoming community [59], and highlights the importance of local contexts for refugee resettlement [15,60].…”
Section: Regional Resettlement In Australiamentioning
confidence: 99%
“…People from refugee backgrounds face difficult challenges during the settlement process. Successful integration into a new society is often complicated by issues such as low or no income [1], housing problems [2, 3], language barriers [4, 5], a lack of social support networks and limited access to healthcare [6]. They may experience discrimination in the labour market, and have limited knowledge of the cultural and social nuances of their new community [7].…”
Section: Introductionmentioning
confidence: 99%
“…Issues surrounding asylum seekers in Australia continue to be subject to acute scrutiny. Although all asylum seekers in Australia are placed in detention centres while their asylum applications are reviewed, some vulnerable and low‐risk asylum seekers are relocated into the community while they await the outcome of their visa application (Vasey & Manderson, ). Due to the mental health problems experienced by asylum seekers, it is important that they have access to appropriate services while living in the community.…”
mentioning
confidence: 99%
“…Those who arrive after this date are not to be resettled in Australia, regardless of the outcome of their application in a bid to deter further arrivals (Department of Immigration and Border Protection, ). However, those who arrived before this date have the possibility of being relocated from detention centres into the community, on a Bridging Visa E or as part of the community detention programme, while they wait for their claim to be processed (Vasey & Manderson, ). Other people who arrived in Australia lawfully (i.e., on student visa) but who subsequently applied for asylum are typically not placed in a detention, but instead stay in the community while their claim is processed.…”
mentioning
confidence: 99%